Monomorphic epitheliotropic intestinal T-cell lymphoma presenting with jejunal perforation: A challanging diagnosis - Shukla, Anju; Dabadghao, Sunil Sharad; Singh, Poonam (Indian Journal of Case Reports, 2020)
Monomorphic epitheliotropic intestinal T-cell lymphoma (MEITL) is an extremely rare and highly aggressive form of primary intestinal T-cell lymphoma previously classified as type II enteropathy-associated T-cell lymphoma (EATL). It has no clear association with coeliac disease and has varied non-specific clinical presentations and radiological findings. Herein, we discuss a case of MEITL presenting as jejunal perforation that was initially considered to be tuberculosis. Even in the presence of well-established epidemiological, histopathological, and immunophenotypic features, the diagnosis was delayed.